Relationship of Inter‐Individual Blood Pressure Variability and the Risk for Recurrent Stroke - Bum Joon Kim; Sun U. Kwon; Dalia Wajsbrot; Jaseong Koo; Jong Moo Park; Barrett W. Jeffers (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2018)
Background Evidence suggests that patients with higher blood pressure variability (BPV) have a higher risk for stroke, but any link between BPV and stroke recurrence is unknown among those who had a stroke or transient ischemic attack (TIA). Methods and Results Data for patients with a history of stroke or TIA at enrollment were extracted from the ASCOT (Anglo Scandinavian Cardiac Outcomes Trial) and the ALLHAT (Antihypertensive and Lipid‐Lowering Treatment to Prevent Heart Attack Trial). BPV was defined as the within‐subject standard deviation or coefficient of variation of systolic blood pressure across visits from 12 weeks poststroke or TIA onward. BPV was significantly higher in patients with a history of stroke or TIA than those without. BPV was a predictor of recurrent stroke in the pooled analysis. In the ASCOT study, 252 patients (12.3%) had a recurrent stroke among 2046 with a history of stroke. Incidence of recurrent stroke was significantly higher in the highest BPV quartile (17.8%) compared with the lowest quartile (10.5%); by treatment arm, this reached significance for the amlodipine‐arm only (high‐BPV: 18.7% versus low‐BPV: 12.9%; P=0.029). Of the 2173 patients from the ALLHAT with a history of stroke or TIA, patients with the highest quartile of BPV had a higher incidence of recurrent stroke (9.6%) compared with the lowest quartile BPV (5.5%); by treatment arm, this reached significance for the chlorthalidone‐arm only (high‐BPV: 12.1% versus low‐BPV: 5.4%; P=0.007). Conclusions Visit‐to‐visit BPV is a predictor of recurrent stroke in patients with a history of stroke or TIA on antihypertensive treatment. Considering BPV following a stroke may be important to reduce the risk for a recurrent stroke.